All about anaesthesia - Davies, Jan (Oxford University Press, 2000)
The aim of this book is to explain what anaesthesia is, to describe how anaesthetics are given, and to detail how anesthetists care for you. The authors, both senior anaesthethists, show how anaesthetists can affect you and how you can affect your anaesthetic. Much of this information will come from the following course of seven patients as they make their way to and from the operating room